Economic outcomes of sequences which include monoclonal antibodies against vascular endothelial growth factor and/or epidermal growth factor receptor for the treatment of unresectable metastatic colorectal cancer. (February 2014) - Rautenberg, T.; Siebert, U.; Arnold, D.; Bennouna, J.; Kubicka, S.; Walzer, S.; Ngoh, C.
Abstract Background: Patients with unresectable, metastatic colorectal cancer with wild type Kirsten ras mutational status are eligible for sequential treatments which include monoclonal antibodies as first line (1L), second line (2L), or third line (3L) regimens. Objective: To compare the economic outcomes of different sequences which include monoclonal antibodies for the treatment of unresectable metastatic colorectal cancer. Methods: Individual drug regimens for 1L, 2L, and 3L treatments were compiled according to the clinical studies in the Summary of Product Characteristics for monoclonal antibodies. They were combined into plausible treatment sequences. Health outcomes were approximated using additive median PFS benefit, and economic outcomes were calculated with a treatment sequencing costing tool. Limitations of the analysis include the clinical trial data sources, cost assumptions, and the additive PFS approach. Results: Seventeen sequences were evaluated. Results of the analysis show that sequences including 1L anti-EGFRs generally have relatively low-to-medium health outcomes at the highest comparative sequence costs compared to sequences including 2L anti-EGFRs, which have lower health outcomes at the lowest cost. Sequences including 3L anti-EGFRs (sequential bevazicumab-based 1L and 2L) have the highest health outcomes, with potential cost savings of €5972–€11, 676 if replacing 2L anti-EGFRs or an additional cost of €5909–€12, 708 if replacing 1L anti-EGFR regimens. Conclusion: Clinical sequences consisting of 1L and 2L line bevacizumab followed by 3L anti-EGFR potentially yield the greatest health outcomes associated with a reasonable trade-off in additional cost when replacing 1L anti-EGFRs and are potentially cost-saving if replacing 2L anti-EGFRs, per patient per lifetime. To maximize health outcomes, optimal sequences include anti-EGFRs as 3L regimen, with an approximately equivalent trade-off in costs between the most costly (anti-EGFR 2L) and least costly (anti-EGFR 1L) sequences.